Rosendaal linear interpolation method appraising of time in therapeutic range in patients with 12-week follow-up interval after mechanical heart valve replacement - Zhu, Xiliang; Xiao, Xijun; Wang, Sheng; Chen, Xianjie; Lu, Guoqing; Li, Xiaoyang (Frontiers in Cardiovascular Medicine, 2022)
Background The objective of this study was to evaluate the quality of anticoagulation by the time in therapeutic range (TTR) for patients with 12-week INR follow-up interval. Materials and methods From January 2018 to December 2020, a selective group of patients who underwent mechanical valve replacement and followed up at our anticoagulation clinic for adjustment of warfarin dose were enrolled. The incidences of complications of anticoagulation therapy were reported by linearized rates. TTR was calculated by the Rosendaal linear interpolation method. Results Two hundred and seventy-four patients were eligible for this study. The mean age of these patients was 52.8 ± 12.7 years, and 65.7% (180 cases) of them were females. The mean duration of warfarin therapy was 16.7 ± 28.1 months. A total of 1309 INR values were collected, representing 66789 patient days. In this study, the mean TTR was 63.7% ± 18.6%, weekly doses of warfarin were 20.6 ± 6.0 mg/weekly, and the mean monitoring interval for the patient was 53.6 ± 27.1 days. There were 153 cases in good TTR group (TTR ≥ 60%) and 121 cases in poor TTR group (TTR < 60%). The calculated mean TTR in both groups was 42.6% ± 22.1% and 74.8% ± 10.4%, respectively. Compared with the TTR ≥ 60% group, the TTR < 60% group exhibited a more prevalence of female gender (p = 0.001), atrial fibrillation (p < 0.001), NYHA ≥ III (p < 0.001), and lower preoperative left ventricular ejection fraction (LVEF, p = 0.032). In multivariate analysis, female gender (p = 0.023) and atrial fibrillation (p = 0.011) were associated with TTR < 60%. The incidence of major bleeding and thromboembolic events was 2.7% and 1.1% patient-years, respectively. There was one death which resulted from cerebral hemorrhage. The incidence of death was 0.5% patient-years. The difference in anticoagulation-related complications between the TTR < 60% group and the TTR ≥ 60% group was not statistically significant. Conclusion For patients with stable international normalized ratio monitoring results who are follow-up at anticoagulation clinics, a 12-week monitoring interval has an acceptable quality of anticoagulation. The female gender and atrial fibrillation were associated with TTR < 60%.